Unveiling the Potential of Cannabinoids in Multiple Sclerosis and the Dawn of Nano-Cannabinoid Medicine - Roua A. Nouh; Ahmed Kamal; Oluwaseyi Oyewole; Walaa A. Abbas; Bishoy Abib; Abdelrouf Omar; Somaia T. Mansour; Anwar Abdelnaser (MDPI AG, 2024)
Multiple sclerosis is the predominant autoimmune disorder affecting the central nervous system in adolescents and adults. Specific treatments are categorized as disease-modifying, whereas others are symptomatic treatments to alleviate painful symptoms. Currently, no singular conventional therapy is universally effective for all patients across all stages of the illness. Nevertheless, cannabinoids exhibit significant promise in their capacity for neuroprotection, anti-inflammation, and immunosuppression. This review will examine the traditional treatment for multiple sclerosis, the increasing interest in using cannabis as a treatment method, its role in protecting the nervous system and regulating the immune system, commercially available therapeutic cannabinoids, and the emerging use of cannabis in nanomedicine. In conclusion, cannabinoids exhibit potential as a disease-modifying treatment rather than merely symptomatic relief. However, further research is necessary to unveil their role and establish the safety and advancements in nano-cannabinoid medicine, offering the potential for reduced toxicity and fewer adverse effects, thereby maximizing the benefits of cannabinoids.